Prevalence of Salmonella in Stool During the Vaccine Impact on Diarrhea in Africa (VIDA) Study, 2015–2018. (19th April 2023) - Kasumba, Irene N; Powell, Helen; Omore, Richard; Hossain, M Jahangir; Sow, Samba O; Ochieng, John Benjamin; Badji, Henry; Verani, Jennifer R; Widdowson, Marc-Alain; Sen, Sunil; Nasrin, Shamima; Permala-Booth, Jasnehta; et al.
Abstract: Background: Non-typhoidal Salmonella (NTS) is a common cause of gastroenteritis in young children, with limited data on NTS serovars and antimicrobial resistance in Africa. Methods: We determined the prevalence of Salmonella spp. and frequency of antimicrobial resistance among serovars identified in stools of 0–59 month-old children with moderate-to-severe diarrhea (MSD) and controls enrolled in the Vaccine Impact on Diarrhea in Africa (VIDA) Study in The Gambia, Mali, and Kenya in 2015–2018, and compared with data from the Global Enteric Multicenter Study (GEMS; 2007–2010) and the GEMS-1A study (2011). Salmonella spp. was detected by quantitative real-time PCR (qPCR) and culture-based methods. Identification of serovars was determined by microbiological methods. Results: By qPCR, the prevalence of Salmonella spp. among MSD cases was 4.0%, 1.6%, and 1.9% and among controls was 4.6%, 2.4%, and 1.6% in The Gambia, Mali, and Kenya, respectively, during VIDA. We observed year-to-year variation in serovar distribution and variation between sites. In Kenya, Salmonella enterica serovar Typhimurium decreased (78.1% to 23.1%; P < .001) among cases and controls from 2007 to 2018, whereas serogroup O:8 increased (8.7% to 38.5%; P = .04). In The Gambia, serogroup O:7 decreased from 2007 to 2018 (36.3% to 0%; P = .001) but S. enterica serovar Enteritidis increased during VIDA (2015 to 2018; 5.9% to 50%; P = .002). Only 4 Salmonella spp. were isolated in Mali during all 3 studies. Multidrug resistance was 33.9% in Kenya and 0.8% in The Gambia across all 3 studies. Ceftriaxone resistance was only observed in Kenya (2.3%); NTS isolates were susceptible to ciprofloxacin at all sites. Conclusions: Understanding variability in serovar distribution will be important for the future deployment of vaccines against salmonellosis in Africa.